Eliminativism in philosophand the attack to scientific psychology - Braun, Ricardo (2008)
In this paper the current theories of eliminativism are discussed. Eliminativism is the radical reductionist program of mental terms and causal explanation as it is used in psychology which presupposes the concepts of beliefs and desires. Although the use of beliefs and desires is commonplace in the so-called “Folk psychology”, ultimately scientific psychology utilizes those categories as well, and therefore, eliminativism is also an attack to scientific psychology. The theses of P. M. Churchland, P. S. Churchland and S. Stich are discussed and I shall demonstrate that eliminativism is an inadequate program due to: 1) the unique nature of pschological explanations; 2) our self-notion as rational beings; and 3) pragmatic concerns.